The Legal Regime of Surface and Underground Waters - Szalma, József (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
In this paper the author analyzes the Serbian and foreign laws regulating the issue of quality of surface and underground water. He points out that, due to the interconnection between surface and underground waters, the management of the issue of their quality requires an integral approach. The basic legal instrument for the quality management of waters is the water-use permit and the consent for industrial (special) utilization of waters, which are based on the registry on the status of waters and on the supervision of the fulfillment of the conditions set-out in permits. Concerning the issue of eligibility of the new beneficiaries of water-use permits, the author refers to the legislation of the European Union and to the national legislation of member states. They prescribe the instruments of preliminary environmental analysis and environmental permit that aim to assess the impact of new industrial facilities on the quality of waters and the envisage means of elimination of environmental hazards, which might potentially realize from the industrial facilities.